Pattern and Interpretation of Injuries Due to fall from Height in a Hilly State of North India: An Autopsy based Stud - Abhishek Sharma; Pankaj Pathania; Aditya Kumar Sharma; Piyush Kapila; Dhruv Gupta (Indian Journal of Forensic Medicine and Pathology, 2025)
Introduction: A fall from considerable height followed by landing on a surface can lead to multiple injuries which can be sustained during the fall or after landing on the ground. The injuries sustained after a fall from height can vary from an abrasion or contusions to more severe injuries like fractures, head injury, injury to the visceral organs or even death. This study was conducted to interpret the injuries caused due to fall from a considerable height and their medicolegal interpretation in cases brought for autopsy to a Tertiary Care Hospital of Northern India. Aims and Objectives: To study the pattern of distribution of external and internal injuries in autopsy cases of deaths caused by a fall from height and to analyze their demographic characteristics. Methodology: This cross-sectional study was conducted over a period of one and a half years from 1st January’ 2020 to 30th December’ 2020 in the Department of Forensic Medicine, Indira Gandhi Medical College, Shimla. Results: During our study period, 125 (26%) cases were of fall, out of which, most of the cases were in the age group of 51-60 years (22.4%), 110 (88%) were males. The commonest region sustaining the primary impact was Head in 98 (78.4%) cases. The intracranial 𿿿ndings were present in 105 cases. The internal thoracic injury was present in 57 cases. The spinal fractures were found in 33 cases. The abdominal visceral injuries were found in 18 cases. 55 (44%) cases suffered fall from a height of 10-20 feet. Conclusion: This study highlights that falls remain a signi𿿿cant cause of mortality, accounting for 26% of the total autopsy cases examined during the study period. The most affected demographic was middle-aged adults, particularly those between 51–60 years, with a notable male predominance (88%). the study underscores the urgent need for preventive strategies, especially in rural and occupational settings, as well as improvements in pre-hospital care and trauma management to reduce fall-related fatalities.